Effect of sowing dates and NPK levels on active substances in seeds of isabgol plants (Plantago ovata Forsk, L.). - Massoud Hekmat, Y. A.; Hussein, H. A. A.; El-Gamal Seham, M. A. (International Journal of Horticultural Science, 2002)
Two field experiments were carried out in the Experimental Station and Laboratory of the Vegetables and Floriculture Dept., Fac. of Agric., Mansoura Univ., during the winter seasons of 1995/96 and 1996/97. The investigation aimed to study the effect of different sowing dates and NPK fertilization levels, as well as their interactions on active substances extracted from Isabgol plant (mucilage contents). Four sowing dates and six NPK levels were studied. The main findings in this investigation can be summarized as follows: • Plants grown in the first sowing data (Nov. 1st week) produced the highest content of mucilage as g/5 g seeds or as percentage of mucilage per plant. • The addition of NPK fertilization significantly increased the mucilage content of seed and its percentage per plant. The highest content and percentage were in plants treated with the fourth level of NPK (178.0 g/3m2). • Concerning effect of interaction between sowing dates and NPK levels on mucilage content, the highest content and percentage per plant were produced in plants grown in the first sowing date and treated with the fourth level of NPK.